Child rearing practices at infant toddler center and at home: a case study - Bravo Soto, Astrid (2018)
Infant entrance to formal education spaces installs them in a different context, with new people, things and dynamic. The article reports part of a study who explores the exchange about child rearing practices between families and a day care center. Child rearing practices of different contexts, the exchanges that take place about this and how is gathered in the curriculum are described. It is noted that infant - toddler classroom practices are based on rights approach, activities are emphasized by pedagogic purposes and a good treatment to the child is improved. In the familiar context, affective contact with infants is prioritized. The incorporation of knowledge concerning rearing practices in the proposal curriculum is still incipient.